Calcium Hydroxide Chlorides: The Ternary System Ca(OH)2‐CaCl2‐H2O at 25, 40, and 60 °C, Phase Stoichiometry and Crystal Structure. Issue 10 (9th May 2019) - Häusler, Felix; Schmidt, Horst; Freyer, Daniela
Abstract : The formation of calcium hydroxide chlorides is an important issue in processes of the chemical raw materials industry, in terms of purification of flue gases, and concrete/cement corrosion. Current information on phase compositions given in the literature are contradictory. In this work systematic solubility studies were carried out at 25, 40, and 60 °C in the system Ca(OH)2 ‐CaCl2 ‐H2 O and the compositions of the ternary solid phases were precisely determined using the Schreinemakers' method. Two ternary phases were identified, the hydrate 3Ca(OH)2 · CaCl2 · 12H2 O and the anhydrous calcium hydroxide chloride Ca(OH)2 · CaCl2 . The crystal structure of 3Ca(OH)2 · CaCl2 · 12H2 O was solved by means of single‐crystal X‐ray diffraction at –123 °C (150 K). Abstract :